PHYTOCHEMICAL CONSTITUENTS AND HYPOGLYCEMIC EFFECT OF GYMNEMIC ACID EXTRACTS FROM BIG AND SMALL LEAF VARIETIES OF Gymnema Sylvestre R.Br - Ramar Krishnamurthy; D. A. Animasaun; R. T. Patel; R. S. Ingalhalli (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2016)
Phytochemical and hypoglycemic effects of two varieties of Gymnema sylvestre were studied. The leaves of Big-leaf (MCL) and the small-leaf (ZMGL) varieties were grown in Uka Tarsadia University, Bardoli, India. Water, ethanol, methanol, petroleum ether, haxane and chloroform were used for phytochemical extraction from the dried leaves. Gymnemic acid was extracted and purified from the two varieties by Thin Layer Chromatography (TLC). Four groups of matured whisker rats (six per group) were induced with high-glucose level. Three groups were treated with standard drug Glibenclamide (5mg/kg), gymnemic acid extracts from MCL and ZMDL respectively while the fourth group served as experimental control. Hypoglycemic activities of extracts were evaluated using animals’ blood sample. Result showed water and methanol are best solvents for phytochemical extraction from the plant and the yield is higher in ZMGL than MCL. Also, gymnemic acid yield varied. From the results, hypoglycemic activities from the animals’ blood revealed that treatments from both MCL and ZMGL are not significantly different from standard drug Glibenclamide. The study concluded that water or methanol is appropriate solvent for phytochemical extraction from G. sylvestre leaves and extract from both lines of the plant could be utilized to reduce blood glucose levelKeywords: phytochemical extraction, extraction solvents, gymnemic acid, hypoglycemic effects